Analisis Penerapan Project Based Learning untuk Meningkatkan Hasil Belajar Matematika Madrasah Ibtidaiyah Palangkaraya - Erviana, Diva; Mahmudah, Istiyati (Universitas Islam Negeri Raden Fatah Palembang, 2023)
This research aims to determine the learning outcomes of grade 6 students in mathematics subjects after implementing the project-based learning model. As we know, mathematics is a science that has abstract concepts so it is difficult for elementary school students who have a concrete way of thinking to understand. For this reason, teachers need to understand learning models that can help teachers create a pleasant learning atmosphere for students. This reasearch is a type of descriptive qualitative research using direct observation data collection techniques at MIN 2 Palangka Raya City and interviewing grade 6 teachers there. The source of data obtained was from interview with teachers. Then the data obtained from the interview was analyzed using descriptive data analysis techniques, which later described the data so that conclusions were obtained that answered the questions clearly. After carrying out the analysis and obtaining answers realted to the problems asked, the implementaion of Project Based Learning turned out to pla a very important role in improving srudent learning outcomes.